Grandma elephant's in charge - Jenkins, Martin, 1959-; Bates, Ivan (Cambridge, Mass. : Candlewick Press, 2003)
Describes the behavior of elephants in a family group, particularly the role of the older female elephants.
Keywords: Elephants -- Behavior -- Juvenile literature; Familial behavior in animals -- Juvenile literature; Elephants; Familial behavior in animals